Synergies between spectroscopic and asteroseismic surveys for the Kepler field with LAMOST. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Fu, Jian-Ning; De Cat, Peter; Ren, An-Bing; Yang, Xiao-Hu; Catanzaro, Giovanni; Corbally, Christopher; Frasca, Antonio; Gray, Richard; Molenda-Żakowicz, Joanna; Shi, Jian-Rong; Luo, A-Li; Zhang, Hao-Tong; et al.
Abstract: The NASA Kepler satellite has provided unprecedented high duty-cycle, high-precision light curves for a large number of stars by continuously monitoring a field of view in Cygnus-Lyra region, leading to great progress in both discovering exoplanets and characterizing planet-hosting stars by means of asteroseismic methods. The asteroseismic survey allows the investigation of stars covering the whole H-R diagram. However, the low precision of effective temperatures and surface gravities in the KIC catalogue and the lack of information on chemical composition, metallicity and rotation rate prevent asteroseismic modeling, requiring spectroscopic observations for thousands of asteroseismic targets in the Kepler field in a homogeneous way.